2017
DOI: 10.2139/ssrn.2940429
|View full text |Cite
|
Sign up to set email alerts
|

Community-Level Flood Mitigation Effects on Household-Level Flood Insurance and Damage Claims Payments

Abstract: The Community Rating System (CRS) was introduced to encourage community-level flood mitigation and increase household-level National Flood Insurance Program (NFIP) participation. It is not clear, however, if and to what extent community participation in the CRS increases household participation in the NFIP and decreases damage claims payments. We employ genetic matching methods and estimate fixed-effects and Mundlak-style panel regression models that control for key geospatial, socioeconomic, and time effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It has received considerable attention in the recent academic literature. Most of these studies focus on the determinants of community participation in the CRS (Landry and Li 2012;Sadiq and Noonan 2015a;Li and Landry 2018), adaptive capacity (Posey 2009), policy learning ), the nonlinear incentive structure of the CRS (Sadiq and Noonan 2015b), the effects of the CRS on flood insurance demand (Dixon et al 2006;Zahran et al 2009), and flood insurance claims (Michel-Kerjan and Kousky 2010;Frimpong and Petrolia 2016). Communities with greater flood risk are more likely to participate in the CRS, although participation rates also follow from the size of the community's government personnel (Sadiq and Noonan 2015a), flood experience and share of senior citizens (Landry and Li 2012), and population density ).…”
Section: The Community Ratings Systemmentioning
confidence: 99%
“…It has received considerable attention in the recent academic literature. Most of these studies focus on the determinants of community participation in the CRS (Landry and Li 2012;Sadiq and Noonan 2015a;Li and Landry 2018), adaptive capacity (Posey 2009), policy learning ), the nonlinear incentive structure of the CRS (Sadiq and Noonan 2015b), the effects of the CRS on flood insurance demand (Dixon et al 2006;Zahran et al 2009), and flood insurance claims (Michel-Kerjan and Kousky 2010;Frimpong and Petrolia 2016). Communities with greater flood risk are more likely to participate in the CRS, although participation rates also follow from the size of the community's government personnel (Sadiq and Noonan 2015a), flood experience and share of senior citizens (Landry and Li 2012), and population density ).…”
Section: The Community Ratings Systemmentioning
confidence: 99%
“…The CRS provides incentives for at-risk communities to invest in non-/structural flood protection and damage reduction activities to receive 5% to 45% discounts on NFIP premiums [25]. Researchers have found that the CRS generates incentives for purchases of flood insurance [26][27][28]; preparedness and mitigation, particularly in densely populated and wealthier communities [28]; and results in lower insurance claims from participating communities [1]. However, as designed, it neither generates incentives for communities to adopt more complex flood reduction investments [7,29] nor to incorporate ex situ flood reduction activities.…”
Section: Introductionmentioning
confidence: 99%